(untitled) (Madhyabindu Journal, 2026)
Entrepreneurship plays a transformative catalyst for innovation, job creation and economic prosperity of countries like Nepal. This study examines numerous aspects that shape the entrepreneurial intentions of Master of Business Studies (MBS) students at Madhyabindu Multiple Campus (MMC), an affiliated campus of Tribhuvan University. To investigate the effects of attitude towards the act, perceived opportunity, risk-bearing propensity, and perceived educational support on students’ entrepreneurial aspirations, this study utilized the lens of Planned Behavior. This study adopted a descriptive-cum-analytical research design. Primary data were accumulated using a census method via a structured questionnaire from 79 MBS students. Results exhibit that students have strong entrepreneurial intentions and a positive attitude towards entrepreneurship. There was a significant positive association between all four independent variables and entrepreneurial intention, confirmed by Correlation and Regression analysis. The regression model explained a substantial 34.7% of the variance in entrepreneurial intention, with attitude towards the act emerging as the strongest predictor. The study concludes that even if students have strong aspirations to pursue entrepreneurship, there is probably still a gap between intention and action. Financial limitations and an inadequate institutional support system are two potential obstacles to this. It is recommended to enhance practical entrepreneurship curricula, strengthen mentorship programs, and offer focused institutional support to create a strong entrepreneurial ecosystem within the university.